2016
DOI: 10.4049/jimmunol.1502322
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Antibiotic Treatment Impacts Development of the Neonatal Intestinal Microbiome and Antiviral Immunity

Abstract: Microbial colonization of the infant gastrointestinal tract (GIT) begins at birth, is shaped by the maternal microbiota, and is profoundly altered by antibiotic treatment. Antibiotic treatment of mothers during pregnancy influences colonization of the GIT microbiota of their infants. The role of the GIT microbiota in regulating adaptive immune function against systemic viral infections during infancy remains undefined. We used a mouse model of perinatal antibiotic exposure to examine the effect of GIT microbia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
112
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(125 citation statements)
references
References 57 publications
1
112
2
2
Order By: Relevance
“…These results illustrate that Ag-specific CD8 + T cells derived from MAT mice despite initial priming in a normal microbiota environment under optimal activation conditions, overall maintain a differential phenotype from CTRL Ag-specific CD8 + T cells in exhibiting decreased polyfunctional antiviral cytokine responses. This behavior is consistent with the hypothesis that intrinsic differences in MAT infant CD8 + T cells exist (36) possibly imprinted by their development in a GIM-depleted environment.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…These results illustrate that Ag-specific CD8 + T cells derived from MAT mice despite initial priming in a normal microbiota environment under optimal activation conditions, overall maintain a differential phenotype from CTRL Ag-specific CD8 + T cells in exhibiting decreased polyfunctional antiviral cytokine responses. This behavior is consistent with the hypothesis that intrinsic differences in MAT infant CD8 + T cells exist (36) possibly imprinted by their development in a GIM-depleted environment.…”
Section: Resultssupporting
confidence: 90%
“…We recently reported that infant mice whose mothers were treated with antibiotics (MAT) in the last days of pregnancy and during lactation have significantly altered composition of the GIM, enhanced susceptibility to systemic viral infection, altered innate immune cell populations, and poor effector CD8 + T cell responses compared with CTRL infants (36). Particularly, MAT effector CD8 + T cells are unable to sustain IFN-γ production in vivo following vaccinia virus infection and in vitro upon TCR and CD28 stimulation (36).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Maternal antibiotic treatment, administered during pregnancy and lactation results in profound alterations in the composition of the microbiota in mothers and infants. 10 Prenatal antibiotics are associated with a larger body mass index (BMI) at the age of two years. 11 Children experiencing a higher number of respiratory tract infections in the first year of life already demonstrate an aberrant microbial developmental trajectory from the first month of life on.…”
Section: Antibiotics Early In Lifementioning
confidence: 99%